Skip to content
Related Articles

Related Articles

Improve Article

Class 12 RD Sharma Solutions- Chapter 11 Differentiation – Exercise 11.8 | Set 2

  • Difficulty Level : Hard
  • Last Updated : 13 Jan, 2021

Question 11: Differentiate sin-1(2x√(1-x2)) with respect to tan-1(x/√(1-x2)) if -1/√2<x <1/√2.

Solutions:

Let u = sin-1(2x√(1-x2))

Substitute x = sin θ ⇒ θ = sin-1x

u = sin-1(2 sin θ √(1 – sin2θ))

u = sin-1(2 sin θ cos θ) [sin2θ + cos2θ = 1]



u = sin-1(sin 2θ) —–(i) [sin 2θ = 2 sin θ cos θ]

Let, v = tan-1(x/√(1-x2))

v = tan-1(sin θ/ √(1 – sin2θ))

v = tan-1(sin θ/cosθ) [sin2θ + cos2θ = 1]

v = tan-1(tan θ) —–(ii) [tan θ = sin θ/cos θ]

Here, -1/√2 < x <1/√2

⇒ -1/√2 < sin θ <1/√2

⇒ – π/4 < θ < π/4

So, from equation (i), u = 2 θ [sin-1(sin θ) = θ, θ ∈ (0,π/2)]

u = 2 sin-1x

du/dx = 2/ √(1 – x2) —–(iii) [d(sin-1x)/dx = 1/√(1 – x2)]

From equation (ii), v = θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

v = sin-1x

dv/dx = 1/ √(1 – x2) —–(iv)

Dividing equation (iii) by (iv)

du/dv = 2 (Ans)

Question 12: Differentiate tan-1(2x/(1-x2)) with respect to cos-1((1-x2)/(1+x2)) if 0<x<1

Solutions:

Let u = tan-1(2x/(1 – x2))



Substitute x = tan θ, ⇒ θ = tan-1x

u = tan-1(2 tan θ/(1 – tan2θ))

u = tan-1(tan 2θ) —–(i) [tan 2θ = 2 tan θ/(1 – tan2θ)]

Now, let v = cos-1((1 – tan2θ)/(1 + tan2θ))

v = cos-1(cos 2θ) —–(ii) [cos 2θ = (1 – tan2θ)/(1 + tan2θ)]

Here, 0 < x <1

⇒ 0 < tan θ < 1

⇒ 0 < θ < π/4

So, from equation (i), u = 2θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

u = 2 tan-1x

du/dx = 2/(1 + x2) —–(iii) [d(tan-1x)/dx = 1/(1 + x2)]

From equation (ii), v = 2θ [cos-1(cos θ) = θ, θ ∈ [0 , π]

v = 2 tan-1x

dv/dx = 2/(1 + x2) —–(iv) [d(tan-1x)/dx = 1/(1 + x2)]

Dividing equation (iii) by (iv)

du/dv = 1 (Ans)

Question 13: Differentiate tan-1((x-1)/(x+1)) with respect to sin-1(3x-4x3) if -1/2<x<1/2.

Solutions:

Let u = tan-1((x – 1)/(x + 1))

Substitute x = tan θ ⇒ θ = tan-1x

u = tan-1((tan θ – 1)/(tan θ + 1))



u = tan-1((tan θ – tan π/4)/(1 + tan θ tan π/4))

u = tan-1(tan(θ – π/4) —–(i) [tan(A – B) = (tan A – tan B)/(1 + tan A * tan B]

Here, -1/2 < x < 1/2

⇒ -1/2 < tan θ < 1/2

⇒ -tan-1(1/2) < θ < tan-1(1/2)

So, from equation (i), u = θ – π/4 [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

u = tan-1x – π/4

du/dx = 1/(1 + x2) —–(ii) [d(tan-1x)/dx = 1/(1 + x2)]

Now, let v = sin-1(3x – 4x3)

Substitute x = sin θ

v = sin-1(3 sin θ – 4 sin3θ)

v = sin-1(sin 3θ) —–(iii) [sin 3θ = 3 sin θ – 4 sin3θ]

Here -1/2<x<1/2

⇒ -1/2 < sin θ < 1/2

⇒ – π/6 < θ < π/6

From equation (ii), v = 3θ [sin-1(sin θ) = θ, θ ∈ (-π/2 , π/2)]

v = 3 sin-1x

dv/dx = 3/ √(1 – x2) —–(iv) [d(sin-1x)/dx = 1/√(1 – x2)]

Dividing equation (ii) by (iv)

du/dv = (1/3) * √(1 – x2)/(1 + x2) (Ans)



Question 14: Differentiate tan-1(cosx/(1+sinx)) with respect to sec-1x.

Solutions:

Let u = tan-1(cos x/(1 + sin x))

u = tan-1((cos2(x/2) – sin2(x/2))/(cos2(x/2) + sin2(x/2) + 2sin(x/2)cos(x/2)) [cos 2x = cos2x – sin2x , cos2x + sin2x = 1, sin 2x = 2sin x cos x]

Using [a2 – b2 =(a-b)(a+b) ,and (a+b)2 = a2 + b2 + 2ab],

u = tan-1(((cos(x/2) – sin(x/2)) * (cos(x/2) + sin(x/2)))/(cos(x/2) + sin(x/2))2

u = tan-1((cos(x/2) – sin(x/2))/(cos(x/2 + sin(x/2)))

Dividing numerator and denominator by cos(x/2)

u = tan-1((1 – tan(x/2))/(1 + tan(x/2)))

u = tan-1((tan π/4 – tan(x/2))/(1 + tan(x/2)*tan π/4))

u = tan-1(tan(π/4 – x/2) [tan(A – B) = (tan A – tan B)/(1 + tan A * tan B]

u = π/4 – x/2

du/dx = -1/2 —–(i)

Now, let v = sec-1x

dv/dx = 1/(x√(x2-1)) —–(ii)

Dividing equation (i) by (ii)

du/dv = ½ * (- x√(x2-1)) (Ans.)

Question 15: Differentiate sin-1(2x/(1+x2)) with respect to tan-1(2x/(1-x2)) if -1<x<1.

Solution:

Let u = sin-1(2x/(1+x2))

Substitute x = tan θ ⇒ θ = tan-1x

u = sin-1((2 tanθ/ (1 + tan2θ))



u = sin-1(sin 2θ) —–(i) [sin2θ = 2 tanθ/(1 + tan2θ)]

Now, let v = tan-1(2x/(1 – x2))

v = tan-1(2 tan θ/(1 – tan2θ))

v = tan-1(tan 2θ) —–(ii) [tan 2θ = 2 tan θ/(1 – tan2θ)]

Here, -1<x<1

⇒ -1<tan θ< 1

⇒ – π/4 < θ < π/4

So, from equation (i), u = 2θ [sin-1(sin θ) = θ, θ ∈ (-π/2 , π/2)]

u = 2tan-1x

du/dx = 2/(1 + x2) —–(iii)

From equation (ii), v = 2θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

v = 2tan-1x

dv/dx = 2/(1+x2) ——(iv)

Dividing equation (iii) by (iv)

du/dv = 1 (Ans)

Question 16: Differentiate cos-1(4x3-3x) with respect to tan-1(√(1-x2)/x) if 1/2<x<1.

Solution:

Let u = cos-1(4x3-3x)

Substitute x = cos θ ⇒ θ = cos-1x

u = cos-1(4 cos3θ – 3cos θ)

u = cos-1(cos3θ) —–(i) [cos 3θ = 4 cos3θ – 3cos θ]

Now, let v = tan-1(√(1 – x2)/x)

v = tan-1(√(1 – cos2θ)/cos θ)

v = tan-1(sin θ/cos θ)

v = tan-1(tan θ) —–(ii)

Here, 1/2 < x < 1

⇒ 1/2 < cos θ < 1

⇒ 0 < θ < π/3

From equation (i), u = 3θ [cos-1(cos θ) = θ, θ ∈ [0 , π]

u = 3cos-1x

du/dx = -3/√(1-x2) —–(iii)

From equation (ii), v = θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

v = cos-1x

dv/dx = -1/√(1-x2) —–(iv)

Dividing equation (iii) by (iv)

du/dv = 3 (Ans)

Question 17: Differentiate tan-1(x/√(1-x2)) with respect to sin-1(2x√(1-x2)) if -1/√2<x<1/√2.

Solution:

Let u = tan-1(x/√(1-x2))

Substitute x = sin θ ⇒ θ = sin-1x

u = tan-1(sinθ/√(1 – sin2θ))

u = tan-1(sin θ/cos θ)



u = tan-1(tan θ) —–(i)

And, v = sin-1(2x√(1-x2))

v = sin-1(2 sin θ √(1-sin2θ))

v = sin-1(2 sin θ cos θ)

v = sin-1(sin 2θ) —–(ii)

Here, -1/√2<x<1/√2

⇒ -1/√2 < sin θ < 1/√2

⇒ – π/4 < θ < π/4

From equation (i), u = θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

u = sin-1x

du/dx = 1/ √(1-x2) —–(iii)

From equation (ii), v = 2θ [sin-1(sin θ) = θ, θ ∈ (-π/2, π/2)]

v = 2sin-1x

dv/dx = 2/√(1-x2) —–(iv)

Dividing equation (iii) by (iv)

du/dv = 1/2 (Ans)

Question 18: Differentiate sin-1√(1-x2) with respect to cot-1(x/√(1-x2)) if 0<x<1.

Solution:

Let u = sin-1√(1 – x2 )

Substitute x = cos θ ⇒ θ = cos-1x

u = sin-1√(1 – cos2θ)

u = sin-1(sin θ) —–(i)

And, v = cot-1(x/√(1-x2))

v = cot-1(cos θ/√(1 – cos2θ))

v = cot-1(cos θ/sin θ)

v = cot -1(cot θ)

v = tan-1(tan θ) —–(ii) [tan-1(θ) = cot-1(1/θ)]

Here, 0 < x <1

0 < cos θ <1

0 < θ < π/2

So, from equation (i), u = θ [sin-1(sin θ) = θ, θ ∈ (-π/2 , π/2)]

u = cos-1x

du/dx = -1/ √(1-x2) —–(iii)

And, from equation (ii), v = θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

v = cos-1x

dv/dx = -1/ √(1-x2) —–(iv)

Dividing equation (iii) by (iv)

du/dv = 1 (Ans)

Question 19: Differentiate sin-1(2ax√(1-a2x2)) with respect to √(1-a2x2) if -1/√2<ax<1/√2

Solution:

Let u = sin-1(2ax√(1-a2x2))

Substitute ax = sin θ ⇒ θ = sin-1(ax)

u = sin-1(2sin θ √(1 – sin2θ))

u = sin-1(2 sin θ cos θ)

u = sin-1(sin 2θ) —–(i)

And, let v = √(1-a2x2)

dv/dx = -a2x/ √(1 – a2x2) —–(ii)

Here, -1/√2<ax<1/√2

⇒ -1/√2 < sin θ <1/√2

⇒ – π/4 < θ < π/4

So, from equation (i), u = 2θ [sin-1(sin θ) = θ, θ ∈ (-π/2 , π/2)]

u = 2sin-1(ax)



du/dx = 2a/ √(1 – a2x2) —–(iii)

Dividing equation (iii) by (ii)

du/dv = -2/ax (Ans)

Question 20: Differentiate tan-1((1-x)/(1+x)) with respect to √(1-x2) if -1<x<1 .

Solution:

Let u = tan-1((1-x)/(1+x))

Substitute x = tan θ ⇒ θ = tan-1x

u = tan-1((1 – tan θ)/(1 + tan θ))

u = tan-1((tan π/4 – tan θ)/(1 + tan θ tan π/4))

u = tan-1(tan(π/4 – θ) —–(i) [tan(A – B) = (tan A – tan B)/(1 + tan A * tan B]

Here, -1 < x < 1

⇒ -1 < tan θ < 1

⇒ – π/4 < θ < π/4

So, from equation (i), u = π/4 – θ [tan-1(tan θ) = θ, θ ∈ [- π/2, π/2]]

u = π/4 – tan-1x

du/dx = -1/(1 + x2) —–(ii)

And, v = √(1 – x2)

dv/dx = -2x/(2 * √(1 – x2)) = – x/√(1 – x2) —–(iii)

Dividing equation (ii) by (iii)

du/dv = √(1 – x2)/(x * (1 + x2)) (Ans)

Attention reader! Don’t stop learning now. Participate in the Scholorship Test for First-Step-to-DSA Course for Class 9 to 12 students.




My Personal Notes arrow_drop_up
Recommended Articles
Page :